English Achievement of Non English Students of Sriwijaya University in the Academic Year of 2007/2008 - Erlina; Zuraidah (Politeknik Negeri Sriwijaya, 2010)
The objectives of this study were aimed at describing the English proficiency of the non English major students at Sriwijaya University in the academic year of 2007/2008 and whether or not the English teaching has fulfilled the non English students’ needs in learning English as a foreign language. Further, to identify the reasons it the teaching of English at the non English major programs has not fulfilled the students’ needs. At first, the sample of this study was 390 students from 39 study programs out of 8 faculties. However, due to some technical problems, only 266 students of those 8 faculties participated in this study. Based on the results of the toefl test, it was found out that in general, the law faculty students got the highest average score (418.33) while the FKIP students got the lowest average score (372.64). The results of the questionnaire showed that most of the students felt that the teaching of English at their program had not fulfilled their needs (86%). This might be caused by some conditions. First, the methods used did not meet the students’ expectation in which the students preferred to have discussion and presentation rather than lecturing. Second, there were too many students in one class. Third, only 7.3% of the students stated that they did not have any difficulties in learning English. It means 92.7% of the students still got difficulties in learning English. In addition, 39.7% students consider listening as the most difficult subject and 9.5% choose speaking. Fourth, the time allocated for English was not enough—the students might need 2 or 3 semesters to learn English at university.